Efficacy of 4% Articaine with 1:100,000 Adrenaline as an Effective Alternative for Achieving Anesthesia during Dental Extraction - Asmita Ghosh; Subhransu Basu; Chirantan Maity; Sandeep Pachisia; Sudipto Sahu; Sucharu Ghosh (Wolters Kluwer Medknow Publications, 2019)
Purpose: The purpose of the study is to ascertain the efficacy of 4% articaine with 1:100,000 adrenaline, its duration of action, onset, the field of anesthesia, check patient compliance and complications (if any) during and postsurgery, and assess the degree of pain. Materials and Methods: Ninety-five patients requiring intra-alveolar tooth extraction in mandibular and maxillary arches. Results: Subjective onset of action for inferior alveolar nerve block was from 59 to 90 s and the objective onset of action was from 68 to 90 s. For posterior superior alveolar nerve blocks, the onset of action was from 42 to 68 s, and for infraorbital nerve blocks, it was from 40 to 52 s. The mean duration of anesthesia was 183.6 ± 6.912 min in case of inferior alveolar nerve blocks, 60.735 ± 3.212 min in posterior superior alveolar nerve blocks, and 43.33 ± 3.497 min in infraorbital nerve blocks. Pain scoring by the patients showed a visual analog scale score of 2 ± in inferior alveolar nerve blocks, 3 ± in posterior superior nerve blocks, and 1 ± in infraorbital nerve block. Conclusion: We recommend 4% articaine with 1:100,000 adrenaline as a better anesthetic, as it was more comfortable the patient with less bleeding, more profound, less time of onset, slightly longer duration of action, and comfortable to the surgeon.